The Social Phenomenon in â€œMajelis Ta'limâ€ as The Effective Mean of A Family that Carries Out Islamic Values in Their Home - Triyosoputri, Etikawati (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Currently, the phenomenan that occures in â€œMajelis ta'limâ€ is believed as a means forMuslims to gain religious knowledge that is beneficial to the livelohood and life in theworld as a provision for eternal life in the afterlife. It is mostly held at home andespecially in mosques, and even in public places. The attendant rate is very high overtime, thus causing profit for those who follow the activity. The advantages gained arehorizontal (social) and vertical values (velued by Allah SWT). Home is a basic humanneed. Implementation of an Islamic home is a hope for every Muslim. Just like amuslim womanâ€™s body, the house also needs a â€œhijabâ€. Based on this, then it isexpected to be used to separate private and public spaces. This can be used as anindicator of the application of Islamic values at their home.